2011
DOI: 10.1097/shk.0b013e3181ed8ec9
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Produced IL-12p70 Mediates Hemorrhage-Induced Damage in a Complement-Dependent Manner

Abstract: Hemorrhage and hemorrhagic shock instigate intestinal damage and inflammation. Multiple components of the innate immune response, including complement and neutrophil infiltration, are implicated in this pathology. To investigate the interaction of complement activation and other components of the innate immune response during hemorrhage, we treated mice post-hemorrhage with CR2-fH, a targeted inhibitor of the alternative complement pathway and assessed intestinal damage and inflammation 2 h after hemorrhage. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…1). Similar to previous studies (8), wild type mice sustained significant intestinal damage at 2h post-hemorrhage (HEM). In contrast, Tlr2 -/- mice received significantly less damage than wild type mice when subjected to hemorrhage.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…1). Similar to previous studies (8), wild type mice sustained significant intestinal damage at 2h post-hemorrhage (HEM). In contrast, Tlr2 -/- mice received significantly less damage than wild type mice when subjected to hemorrhage.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies indicated that blood loss due to hemorrhage can induce intestinal damage and inflammation (8). To determine if TLR2 is required for this tissue damage, we removed 30% of the calculated blood volume from wild type (C57Bl/6) and Tlr2 -/- mice and analyzed intestinal villus injury at 2h post-hemorrhage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations